Wunderlich’s syndrome: Three cases of acute spontaneous renal bleeding, conservately treated - Andrea Guttilla (Archivio Italiano di Urologia e Andrologia, 2013)
Wunderlich’s syndrome is a clinical condition defined as a spontaneous renal bleeding of non traumatic origin, contained within the Gerota’s fascia. Wunderlich’s syndrome is rare. Spontaneous bleeding of kidney tumors, either benign or malignant, represents the more common causes. Classically it presents with acute flank pain, tender palpable mass and clinical hemodynamic deterioration. These symptoms are defined as the Lenk’s classic triad. We present three cases of spontaneous renal bleeding.